VALIDITY OF EXONERATION CLAUSE IN STANDART CONTRACT - Helda Mega Maya; Catur Yunianto (Universitas Surakarta, 2022)
The purpose of this article is to find out whether the existence of an exoneration clause in the standard contract can be recognized as valid in the agreement. The research method used is normative legal research that describes various legal issues related to standard contracts, agreements as regulated in article 1338 of the Civil Code that all agreements made in accordance with the law apply as law for those who make them. The approach used is the statutory approach and the conceptual approach. By using secondary data consisting of primary, secondary and tertiary legal materials. Based on the results of the study, it can be seen that in the standard contract there is an exoneration clause. The exoneration clause/standard contract does not fulfill the principle of responsible freedom of contract. The principle of freedom of contract is closely related to the content of the agreement, namely the freedom to determine